2015
DOI: 10.1208/s12249-015-0311-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Artesunate-Loaded Chitosan-Coated Lipid Nanocapsule as a Potential Drug Delivery System Against Breast Cancer

Abstract: Artesunate (ART)--a well-known hydrophobic anti-malarial agent was incorporated in a polymer-lipid hybrid nanocolloidal system for anti-cancer therapeutic. The lipid negatively charged nanoemulsion was formulated by modified hot homogenization method then covered with positively charged chitosan via electrostatic interaction to obtain chitosan-coated lipid nanocapsule (ART-CLN). Physical properties of the system were characterized in terms of size, charge, morphology, drug loading capacity, and physical state.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…In principle, drug encapsulation can improve specificity and bioavailability as well as alter pharmacokinetic properties of the drug. 135 The recent years have seen a remarkable surge of studies exploring various approaches in nanomedicine, ranging from liposomal delivery, [136][137][138][139][140][141] encapsulation with other drugs or biomolecules including transferrin, [142][143][144][145] encapsulation with specific properties such as magnetic or pH-responsive liposomes, [143][144][145][146] novel metal based nanostructures, 146,147 solid lipid nanoparticles (SLNs), and niosomes. 148 In general, these studies have consistently reported positive results with significant enhancements to efficacy and improved selectivity.…”
Section: Enhancement Of Anticancer Activitymentioning
confidence: 99%
“…In principle, drug encapsulation can improve specificity and bioavailability as well as alter pharmacokinetic properties of the drug. 135 The recent years have seen a remarkable surge of studies exploring various approaches in nanomedicine, ranging from liposomal delivery, [136][137][138][139][140][141] encapsulation with other drugs or biomolecules including transferrin, [142][143][144][145] encapsulation with specific properties such as magnetic or pH-responsive liposomes, [143][144][145][146] novel metal based nanostructures, 146,147 solid lipid nanoparticles (SLNs), and niosomes. 148 In general, these studies have consistently reported positive results with significant enhancements to efficacy and improved selectivity.…”
Section: Enhancement Of Anticancer Activitymentioning
confidence: 99%
“…5) Although the mechanism of action of these artemisinin derivatives on malarial parasites has not been elucidated, the injury caused by malarial parasites is presumed to be caused by free radicals generated by a reaction with heme produced in malarial phagocyte cells. [6][7][8][9][10] Recently, it has been reported that artemisinin derivatives also exert anti-tumor activity in cancer cells, [11][12][13][14][15][16][17][18] which has attracted attention for use in anti-cancer drugs. The reported mechanisms that might explain the antitumor activity of artemisinin derivatives include induction of apoptosis through reactive oxygen species (ROS) generation, 11) angiogenesis inhibitory effects, 19) inhibition of hypoxia-inducible factor-1α (HIF-1α) activation by ROS generation, 20) and direct DNA injury.…”
mentioning
confidence: 99%
“…Tran and coworkers employed chitosan-coated lipid nanocapsules with AS aiming drug sustained release profile and enhanced cellular uptake increasing cytotoxicity. The results showed evident antitumor activity against breast cancer lines (MCF-7, MDA-MB-231), compared with free AS [24].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 98%